Lactobacillus gasseri CCFM1255 promotes peripheral estrogen synthesis in ovariectomized rats by modulating the gut microbiome and serum metabolome - Qian Chen; Haiqin Chen; Jianxin Zhao; Wei Chen; Gang Wang (Food Science and Human Wellness)
The decline in ovarian estrogen production is known to have detrimental health consequences and negatively affect the quality of life in menopausal women. Increasing estradiol levels is key to preventing disease in menopausal women. In this study, Lactobacillus gasseri CCFM1255 isolated from healthy infants was found to have a positive effect on estradiol production in ovariectomized rats. CYP19, the key enzyme catalysing the conversion of androgens into estrogens, was upregulated in adipose tissue upon CCFM1255 treatment. Untargeted metabolome analysis and targeted metabolite detection were used to identify the key metabolites altered by CCFM1255 treatment. CCFM1255 treatment significantly improved the serum concentration of glutamine (Gln). A significantly positive correlation was observed between serum Gln and estradiol concentrations. CCFM1255 treatment reshaped the structure of the gut microbiome, which was correlated with certain changes in serum metabolite concentrations. These results indicate that the provision of CCFM1255 as a dietary supplement may be an effective strategy to alleviate menopausal symptoms by increasing circulating estradiol.